Carbonylated Proteins as Key Regulators in the Progression of Metabolic Syndrome - Yuki Kitamura; Shinji Oikawa; Jie Chang; Yurie Mori; Gaku Ichihara; Sahoko Ichihara (Antioxidants, 2023)
Based on the known role of oxidative stress in the pathogenesis and progression of metabolic syndrome, we used two-dimensional gel electrophoresis with immunochemical detection of protein carbonyls (2D-Oxyblot) to characterize the carbonylated proteins induced by oxidative stress in spontaneously hypertensive rats/NDmcr-cp (CP), an animal model of metabolic syndrome. We also profiled the proteins that showed change of expression levels in their epididymal adipose tissue at the pre-symptomatic (6-week-old) and the symptomatic (25-week-old) stages of the metabolic syndrome. Two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) combined with matrix-assisted laser desorption ionization time-of-flight tandem mass spectrometry (MALDI-TOF/TOF MS) was used to analyze proteins extracted from the epididymal adipose tissue. The up-regulated proteins identified at the pre-symptomatic stage were mainly associated with ATP production and redox reaction, while the down-regulated proteins found at the symptomatic stage were involved in antioxidant activity and the tricarboxylic acid (TCA) cycle. Further analysis using the 2D-Oxyblot showed significantly high carbonylation levels of gelsolin and glycerol-3-phosphate dehydrogenase [NAD+] at the symptomatic stage. These results suggest that reduced antioxidant capacity underlies the increased oxidative stress state in the metabolic syndrome. The identified carbonylated proteins, including gelsolin, are potential targets that may act as key regulators in the progression of the metabolic syndrome.